2021
DOI: 10.1186/s40168-021-01164-0
|View full text |Cite
|
Sign up to set email alerts
|

Depth-dependent variability of biological nitrogen fixation and diazotrophic communities in mangrove sediments

Abstract: Background Nitrogen-fixing prokaryotes (diazotrophs) contribute substantially to nitrogen input in mangrove sediments, and their structure and nitrogen fixation rate (NFR) are significantly controlled by environmental conditions. Despite the well-known studies on diazotrophs in surficial sediments, the diversity, structure, and ecological functions of diazotrophic communities along environmental gradients of mangrove sediment across different depths are largely unknown. Here, we investigated ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 87 publications
2
11
0
Order By: Relevance
“…The vertical distribution of electron donors and acceptors showed an obvious impact on microbial functions, such as anaerobic oxidation of methane (AOM) and sulphate reduction [ 21 , 22 ]. Recently, we found that N 2 fixation rate increased while the diversity of diazotrophic communities decreased along the depth of mangrove sediments largely due to the vertical variation of salinity [ 23 ]. However, most of such studies were focused exclusively on the top 20 cm of mangrove sediments, which was considered as the layer with the greatest microbial diversity, biomass and activity [ 6 , 20 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The vertical distribution of electron donors and acceptors showed an obvious impact on microbial functions, such as anaerobic oxidation of methane (AOM) and sulphate reduction [ 21 , 22 ]. Recently, we found that N 2 fixation rate increased while the diversity of diazotrophic communities decreased along the depth of mangrove sediments largely due to the vertical variation of salinity [ 23 ]. However, most of such studies were focused exclusively on the top 20 cm of mangrove sediments, which was considered as the layer with the greatest microbial diversity, biomass and activity [ 6 , 20 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mangrove ecosystems play an important role in biodiversity maintenance, wind protection, dike fixation, carbon storage, and seawater purification ( 2 ). Mangrove soil has a high salinity due to periodic tidal seawater immersion and intense biological salinization of mangroves ( 3 ). Mangrove plants have grown in this habitat for a long time and have specialized a set of adaptive mechanisms different from those of terrestrial or freshwater plants ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Excess nitrate in the estuary results from runoff from terrestrial ecosystems and ultimately flows into the ocean . The neighboring mangrove and oceanic ecosystems have also been reported to harbor numerous heterotrophic ANR microbes even with a relatively low nitrate abundance. ,, To investigate their biogeography across the land–estuary–ocean continuum, we analyzed the taxonomic diversity of heterotrophic ANR bacteria in the mangrove, estuarine, and oceanic ecosystems. Through genomic assembly, we detected 8 out of 589 (mangrove), 38 out of 275 (estuarine), and 43 out of 957 (oceanic) MAGs containing both nasA and nirBD in the metagenomic datasets.…”
Section: Resultsmentioning
confidence: 99%